Musculoskeletal Disorders Analysis Of Indonesian Women Farmers With Quick Exposure Check Method - Dian Palupi Restuputri; Bagos Bagos; Dessi Novianti; Estining Tias; Meilliza Dresanala; Nevin Raditya; Tasya Syafa (Universitas Muhammadiyah Malang, 2021)
The role of women farmers in various regions in Indonesia is very much needed because the need for food in Indonesia is relatively high. The working hours also high, with an average of 35 hours per week. Based on the results of preliminary observations using the Nordic Body Map, it was found that the average female farmer felt pain in the back, neck, upper arms, and wrists. This study uses the QEC (Quick exposure checklist) method. Based on this method, several parts of the body assess the onset of work disorders, namely the neck, back, shoulders or arms, and wrists. Apart from that, there are also psychosocial factors, including work speed and stress. In the QEC method, there is an exposure score calculation to determine what action is taken based on the analysis of the total exposure score. This research was conducted by filling out questionnaires in 36 different regions in Indonesia. Based on the questionnaire results, it was found that female farmers in Indonesia had the highest exposure score of 51.33%. This result can occur due to the increased load carried and the length of time worked.